Measuring Worker Perception on Remote Working Adoption During COVID-19 Pandemic: An Industrial Engineering Perspective: A Case Study in Indonesia for Identifying the Potential New Normal of Work Implementation - Tanika D Sofianti; Ivan Kurniawan; Aditya T Pratama; Jessica Florencia (Engineering Science Letter, 2023)
The COVID-19 which started in late 2019 has led to extraordinary measures by government and commerce, to control and reduce the spread of the virus. Many companies have had to rethink the way they work due to travel restrictions and cancellations of major events. While workers related to production activities as well as system-related workers such as bank tellers, cashiers, medical staff, and distribution operators are still working on site, the majority of the workforce in Indonesia has been encouraged to practice "working from home" or remote working during the pandemic. Remote Working means adapting to new circumstances, battling a new set of distractions, as well as experiencing an unprecedented mix of work and personal life. Committing to work from home without understanding performance indicators and drivers can lead to a company's operational failure. Even though the COVID-19 pandemic measures are decreasing, the need to implement a new normal of work that allows for flexible work arrangements and implementation of remote work is increasing. Therefore, the organization needs to understand and control the measures required to keep the company productive in the new work setting. This is important to maintain organizational resilience against any pandemics and technological disruptions, as well as to ensure organizational sustainability. Seven performance indicators of remote work performance and eight influencing factors have been compiled in this study by reviewing previous research on remote work, virtual teamwork, agile teamwork and knowledge management. Further studies are needed to verify the performance indicators and influencing factors, to reveal the correlations between the measures and to identify the most likely drivers of remote work that may transform an organization to its new setting.